RELATIONSHIP BETWEEN THE PERCEPTION CURRICULUM CREDIT SEMESTER SYSTEM (SKS) WITH ACADEMIC ACHIEVEMENT MOTIVATION IN STUDENTS OF SMAN 78 JAKARTA - Fajriati Nurhidayah; Prasetyo Budi Widodo; Dinie Ratri Desiningrum (Faculty of Psychology, Diponegoro University, 2012)
School education has a major role in improving the quality of eduvation ,00aitems through the students academic achievement motivation. Students academic achievement motivation can be seen by the student perception of the curriculum semester credit system is applied in schools. This research was conducted to determine the relationship between perceptions of curriculum semester credit system with academic achievement motivation in students of SMAN 78 Jakarta.The population was 324 students with 177 students as the sample. Determination of the sample using cluster random sampling technique. Cluster random sampling procedures are sampling conducted by randomization to the group. Data collection using academic achievement motivation scale consists of 35 aitems (α=0,855) and scale perception of curriculum semester credit system, which consists of 33 aitems (α=0,858).Simple regression analysis showed rxy=0,354 and p=0,000 (p<0,05), meaning that there is a significant positive relationship between perceptions of curriculum semester credit system with students academic achievement motivation SMAN 78 Jakarta. These result indicate that the positive perception of the curriculum semester credit system, the higher the academic achievement motivation. Conversely, the more negative perceptions of curriculum semester credit system, the lower the academic achievement motivation. The result of this study indicate that students academic achievement motivation SMAN 78 Jakarta are ini the high category and have a positive perception curriculum semester credit system. Perceptions of achievement motivation variable rate of 12,5%, while 87,5% came from other factors that are not disclosed in this study